Shockwave Therapy After Lavage in Gartner Type II Calcific Rotator Cuff Tendinopathy - V.O. Biliavskyi; O.S. Strafun (TERRA ORTHOPAEDICA, 2026)
Summary. Background. Ultrasound-guided percutaneous irrigation of calcific deposits (lavage) is widely used for calcific rotator cuff tendinopathy, but the added value of focused extracorporeal shockwave therapy (ESWT) after lavage in Gartner type II deposits remains insufficiently studied. Objective. To compare lavage followed by focused ESWT with lavage alone in patients with Gartner type II calcific rotator cuff tendinopathy. Materials and Methods. A prospective comparative cohort study. Group A received lavage, three focused ESWT sessions, a subacromial corticosteroid injection, and physiotherapy; group B received the same without focused ESWT. The primary outcome was total SPADI at 6 months. Results. Sixty-six patients (32 in group A and 34 in group B) with comparable baseline characteristics were analyzed. At 6 months, group A showed superior outcomes for total SPADI (9.57 vs 28.81%; difference −19.24), SPADI pain and disability subscales, and numeric-scale pain at night, at rest, and during activity (all p < 0.01). Residual deposit was smaller in group A (1.43 vs 3.93 mm; p < 0.001). Complete resorption of the calcific deposit was achieved in 62.5% vs 26.5% of patients (OR 4.63), near-complete resorption (≤ 2 mm residual calcification) in 75.0% vs 32.4% (OR 6.27), and significant subjective improvement in 62.5% vs 11.8% (OR 12.50). In both groups, the calcific deposit size decreased significantly, while the difference in absolute reduction was non-significant (p = 0.215). Conclusions. The addition of focused ESWT after lavage was associated with better pain relief, functional recovery, and ultrasound-assessed calcification resorption at 6 months. Because of the non-randomized study design, these findings should be interpreted as associative.